Is smokeless tobacco a healthier option in patients with AUD? A follow-up study during treatment - Lars Lien; Ingeborg Bolstad; Jørgen G. Bramness (BMC, 2024)
Abstract Introduction Smoking is negatively related to mental health, but there is a paucity of research on the relationship between the use of smokeless tobacco, such as snus, and mental health outcomes, especially in people with alcohol use disorders (AUD). The aim of the present study was to examine the development of mental distress and quality of life (QoL) among AUD patients in treatment who did or did not use snus. Method The study included 128 AUD patients (27% female) from three rehabilitation clinics in Eastern Norway who were interviewed at admission, at 6 weeks, and after 6 months. Patients were asked about their mental health-related problems, alcohol, and substance use, QoL, and physical activity. Information about tobacco use was gathered with the questions "Do you smoke cigarettes?" and "Do you use snus?", with follow-up questions "How often?". Result There were 39 current snus users (31%), of which 20 were also current smokers (dual users). Seventy-five patients (59%) were smokers only, and only 14 (11%) patients were abstainers. Those who used snus only had a lower severity of dependence score than the other groups (p < 0.05). The dual use group reported lower QoL than the no tobacco use group. In a regression model adjusted for sex and age, smokers and dual users, but not users of snus, had higher levels of mental distress and poorer QoL compared to nontobacco users (p < 0.05). There were no differences between tobacco groups at follow-ups. Conclusion In this study, among AUD patients, snus users reported QoL and mental distress close to that of non-smokers, indicating a lower problem load among snus users compared to smokers. Implications Previous studies have shown conflicting results regarding the potential harm reduction effect of snus use among patients with AUD who smoke regarding their tobacco use, quality of life and mental health problems. This study suggests that snus use could also be a viable alternative to smoking for patients with addictions.